La rotation des postes : ce qu’en pensent des travailleurs d’une usine d’assemblage automobile - Marie St-Vincent; Nicole Vézina; Bernard Dufour; Yves St-Jacques; Esther Cloutier (Perspectives Interdisciplinaires sur le Travail et la Santé)
A perception survey was carried out on 250 workers in the four production departments of an automobile assembly plant. When the assemblers were away from their workstations, each participated in a short interview conducted by an ergonomist. What emerged from the survey was that barely 11 % of the workers were rotated. Twenty-one percent of the workers said they were for rotation, 33 % stated that they were against it, and 46 % said that their opinion depended on the implementation conditions. When they were asked about the advantages of rotation, the workers responded : reducing monotony (53.8 %), reducing physical constraints (47 %), and improving their health (59 %). The disadvantages mentioned by the workers were more numerous and varied, with the ones most often reported being : the characteristics of the workstations (57 % of the workers), the difficulties related to apprenticeship (30 %), not liking change (20 %), and possible negative impacts on health (19 %). Although the survey does not provide precise answers about the impact of rotation, it gives information on the factors to be considered during its implementation : workstation characteristics, training, people’s characteristics, production, leeway in rotation, and size of the work group.